VOLKANOSTRATIGRAFI DAN PETROGENESIS GUNUNG API PURBA SERTA IMPLIKASINYA TERHADAP PROSES ALTERASI DAN MINERALISASI DAERAH ARJOSARI DAN SEKITARNYA, KABUPATEN PACITAN, PROVINSI JAWA TIMUR - Novianti, Selvia
This is an advanced study dealing with ore deposit and some key genetic characteristics including volcanostratigraphy, petrogenesis, hydrothermal alteration system, and ore mineralization of a new discovery ore mineral prospect in Arjosari district, East Java Province, Indonesia. Regionally, the studied area is a volcaniclastic terrain occupied by Mandalika Formation (Tomm), Arjosari Formation (Toma) intruded by a series of intermediate to acidic plutonic rocks (Tomi), which are dominated by Andesite (an) and Diorite (di) intrusions followed by deposition of Semilir Formation (Tms). The host rock is recognized to be basalt to andesite with various crystal grained sizes and other volcaniclastic rocks. NW ? SE and NE ? SW trending strike-slip faults and appeareance of paleo-volcano might play an important role controlling the formation of the ore deposit prospect. Facies identification of paleo-volcano is done by volcanostratigraphy analysis, the result shows that there are 23 units. Island-Arc Tholeitic tectonic setting is successfully identified by using XRay Fluorescence analysis on nine representative samples. Four ore deposit prospects have been discovered by systematic ASD-Terraspec® sampling on study area. The study area identified as High Suplhidation Epithermal System. Main ores deposit such as gold, covellite, bornite, calchopyrite, and pyrite have been identified. The application of those advanced study in Arjosari district shares some similarities of its key characteristics in comparison to other ore mineral deposits worldwide. Our understanding of the varied interrelationships between near-surface and subvolcanic ore deposition, and volcanic landforms and processes as a corollary, the effectiveness of mineral exploration, would be increased if we could know the potential of the valuable diversity of lithology using those advanced study.